Everywhere that Mary went. - Scottoline, Lisa. (New York : HarperPaperbacks, 1993)
While trying to become a partner at the cutthroat Philadelphia law firm where she works, Mary DiNunzio receives threatening phone calls from a dangerous stalker.
Accelerated Reader AR
Keywords: Women lawyers -- Fiction; Stalking victims -- Fiction; Philadelphia (Pa.) -- Fiction; Mystery fiction